PENINGKATAN MOTORIK KASAR MELALUI KEGIATAN OLAHRAGA MELEMPAR DAN MENANGKAP BOLA PADA ANAK USIA 5–6 TAHUN DI PAUD ABABIL - Tia Malinda; Yolanda Pahrul; Amat Hidayat (STKIP Subang, 2026)
Improving Children’s Gross Motor Skills Through Throwing and Catching Ball Activities in Group B at PAUD Ababil. Thesis. Early Childhood Education Teacher Education Study Program, Faculty of Teacher Training and Education, Universitas Bina Bangsa. The main purpose of this study was to improve children's gross motor skills through throwing and catching ball activities in Group B at PAUD Ababil. This research used Classroom Action Research (CAR) with a collaborative approach. The research was conducted in two cycles, each consisting of four stages: planning, action, observation, and reflection. The subjects of this study were 15 children, consisting of 7 boys and 8 girls. Data were collected through observation and documentation using checklist observation sheets. The data analysis technique used was descriptive qualitative analysis. The results showed that in Cycle I, the average achievement of children's gross motor skills reached 56.66% with the category of Developing as Expected (BSH). In Cycle II, the children's gross motor skills increased significantly to 80.55% with the category of Developing Very Well (BSB). This result indicates that the success indicator of the study had been achieved. Based on the results of the study, it can be concluded that throwing and catching ball activities can improve the gross motor skills of children in Group B at PAUD Ababil.